Bilateral maxillary fourth and fifth molars: An unusual radiographic appearance - Mukesh Khemchand Asrani; Vivek Muljibhai Tarsariya; Juned Mustak Pathan (Wolters Kluwer Medknow Publications, 2016)
Distomolars are supernumerary teeth present distal to third molars. Although many cases of bilateral fourth molars are reported, very few cases having bilateral fifth molars are described in literature. Here, we present a case having bilateral impacted maxillary fourth and fifth molars with the fifth molar on the left side having an unusually small appearance.